Forward Kinematics and Workspace Analysis of a 6-DOF Dual-arm Operating System Based on the Screw Theory - Zheng Xuekai; Liu Fang; Yang Yan; Wei Wenqing (Jixie chuandong)
The trajectory planning and control of the manipulator are based on forward kinematics analysis. At present, the analytical method mainly used is the D-H parameter method. This study proposes a screw theory method which is faster and simpler in terms of calculation than the D-H method. The kinematics modeling and forward kinematics equation of dual-arm operating system are established by product of exponentials formula. Simpack software is used to simulate and analyze the dual-arm operating system. The correctness of the forward kinematics model established by screw theory is verified by comparing the simulation results with the results obtained by the forward kinematics equation. Matlab software is used to analyze the workspace, and the workspace of the dual-arm operating system is obtained by comparing the workspace cloud map.